AKT-pathway Inhibition in Chronic Lymphocytic Leukemia Reveals Response Relationships Defined by TCL1 - Schrader, Alexandra; Popal, Wagma; Lilienthal, Nils; Crispatzu, Giuliano; Mayer, Petra; Jones, Dan; Hallek, Michael; Herling, Marco (Current Cancer Drug Targets, 2014)
Cell survival in chronic lymphocytic leukemia (CLL) largely depends on B-cell receptor-induced AKT activation. Gain-of-function genomic lesions of PI3K-AKT-mTOR pathway components are usually absent in CLL. We previously established that a BCR-mediated growth response in CLL is determined by the oncogene T-cell leukemia 1 (TCL1) through a sensitizer effect on AKT phospho-activation. Despite high clinical response rates following AKTcascade inhibition in CLL, resistances in a substantial proportion of patients call for reliable pre- and post-exposure strata to better predict compound responses. Using a panel of inhibitors with differential vertical affinities in the PI3K-AKTmTOR axis, we describe distinct patterns and determinants of sensitivities in 75 CLL samples. The compounds specifically impacted the BCR-induced physical TCL1-AKT interaction. In general, there was an efficient and tumorselective abrogation of cell survival in suspension or protective stromal-cell cultures. However, biochemical and survival responses were heterogeneous across CLL and showed only incomplete overlap across inhibitors. Sensitivity clusters could be defined by differential responses to selective pan-PI3K inhibition vs. compounds acting more down-stream. An elevated PI3K/AKT/mTOR activation state conferred sensitivity or resistance, depending on the applied inhibitor. In fact, down-stream interception by mTOR or dual mTOR/PI3K inhibition appears more efficient in cases expressing the BCRresponse and poor-risk determinants of ZAP70 or TCL1. Finally, exploiting the TCL1-AKT interaction, peptide-based TCL1-interphase mimics were potent in steric AKT antagonization and in reducing CLL cell survival. Overall, this study provides informative response relationships in AKT-pathway interception that can help refining predictive models in BCR-pathway inhibition in CLL.
Keywords: TCL1